2019
DOI: 10.36743/medikes.v6i2.183
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Relaksasi Nafas Dalam Terhadap Penurunan Intensitas Nyeri Haid Pada Remaja Putri Di Man Insan Cendekia Halmahera Barat

Abstract: Dysmenorrhea is the most common complaint that causes young women to go to the doctor for consultation and treatment (Winknjosastro, 2007). The prevalence of dysmenorrhea in several studies shows a fairly high frequency. In a WHO systemic review, the average incidence of dysmenorrhea in young women was between 16. 8 -81%. Research Objectives: To Know The Effect Of Giving Relaxation In Breath Against Decreasing Intensity of Menstrual Pain in YoungWomen in MAN Insane Scholar West Halmahera. Research Methods: Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The fourth study was conducted by Suaib (2019) [9] obtained the results of statistical tests which showed that there was an effect of deep breathing relaxation techniques on the reduction of dysmenorrhea in adolescents, the p-value was 0.0001, which means <α 0.05. The results also showed a decrease in the average dysmenorrhea before and after the intervention by as much as 2.52 points.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth study was conducted by Suaib (2019) [9] obtained the results of statistical tests which showed that there was an effect of deep breathing relaxation techniques on the reduction of dysmenorrhea in adolescents, the p-value was 0.0001, which means <α 0.05. The results also showed a decrease in the average dysmenorrhea before and after the intervention by as much as 2.52 points.…”
Section: Resultsmentioning
confidence: 99%
“…[16] The effect of deep breathing relaxation techniques on reducing dysmenorrhea in adolescents has been proven in research Siregar et al (2015) [6], that before the deep breathing relaxation technique was carried out the majority of 53.33% of respondents felt moderate pain, while after being given deep breath relaxation for at least 5 minutes, the majority of 76.67% of respondents felt mild pain intensity and no more felt severe pain. In research Suaib (2019) [9] also proved that before the deep breathing relaxation technique was carried out as many as 92.59% of respondents experienced moderate pain, then after being given breath relaxation in 30 minutes it was found that 48.14% of respondents experienced mild pain and there was also an increase in those who did not experience menstrual pain 29.63% of respondents. Based on this study, deep breathing relaxation techniques can be done with a minimum time of 5 minutes to 30 DOI 10.18502/kls.v7i2.10344 IVCN minutes because in that time it can already provide a decrease in dysmenorrhea in adolescents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Berbagai cara menangani diantaranya adalah kompres hangat bagian perut yang kram atau kejang selama 10 menit dengan suhu air 45°C (Maidartati et al, 2018), teknik relaksasi nafas dalam untuk relaksasi otot dan memperlancar peredaran darah (Suaib, 2019).…”
Section: Pendahuluanunclassified